Augmented Reality Introduction to Computer Hardware using Tracking Method in UPI "YPTK" Computer System Labor, Padang - Ravhis Al Amin; Randy Permana; M.Hafizh (Jurnal KomtekInfo, 2020)
Technology Augmented Reality is one of the digital industries related to the industrial revolution 4.0. Augmented Reality allows the expansion of the perspective of an object by utilizing digital projections of the object. This technology utilizes sensory such as visual, auditory, haptic, somatosensory, and olfactory to support the delivery of information to users. One of the very potential fields in implementing Augmented Reality is the world of education. Augmented Reality allows students to get a more learning experience interactive and varied, so as to be able to encourage interest and curiosity in learning. In this study, Augmented Reality is used as a medium for learning the introduction of computer hardware to users (students) by utilizing the smartphone and hardware basics of a computer. Users will be presented with an expansion of information in both 3D visuals, audio and video to the device. The results of Augmented Reality are expected to be a supporting media in helping the teaching and learning process in the midst of preparation for facing the industrial revolution 4.0.